Factors influencing patient and health care delays in Oropharyngeal Cancer - Markus Nieminen; Timo Atula; Leif Bäck; Antti Mäkitie; Lauri Jouhi; Katri Aro (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The incidence of human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma (OPSCC) is increasing. Patients with HPV-associated and HPV-unassociated OPSCC differ in many aspects, which may also impact their diagnostic and management timelines. This study aims at studying the patient, primary health care (PHC) and specialist-care (SC) delays and possible differences between these two patient groups in seeking medical care. Methods We reviewed all new patients with OPSCC treated between 2016 and 2018 at our institute, which covers a referral area of 1.6 million people. We collected data on patients’ symptoms and factors influencing why they sought medical care using a patient-reported questionnaire and hospital records. We compared delays based on patient and tumor characteristics. Results In our study population of 83 patients, the median patient delay was 30 days (range, 0–366), with a median PHC delay of 15 days (range, 0 days–2.5 years), and a median SC delay of 54 days (range, 12–231). The SC delay was further divided into diagnostic hospital delay and treatment delay, each with a median length of 16 days (range, 0–237) and 29 days (range, 0–73), respectively. Furthermore, we found that p16 status did not associate with delays. A longer patient delay associated with specific tumor factors, such as a larger primary tumor and a lower UICC 7th edition stage. Patients that had multiple visits or did not have a follow-up visit scheduled at the initial appointment had longer PHC delays. Treatment delay was significantly longer for patients scheduled for (chemo-)radiotherapy than for those undergoing surgery with or without (chemo-)radiotherapy. Conclusions Although delays remained short for the majority of OPSCC patients, long delays require further evaluation and improvement of management. Awareness of presenting symptoms among cancer risk patients and prompt referral practice or a follow-up visit at PHC represent key factors to shortening these delays. Ultimately, the causes for delays in SC appear multifactorial and require institutional quality control.